RETRACTED: Studying temperature and moisture conditions of building envelopes using a condensation nomogram - Zubarev K.P.; Rynkovskaya M.; Fedoseev V.D.; Sapronova Y.A. (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 549, 00001 (2024), https://doi.org/10.1051/e3sconf/202454900001